(untitled) (Third Sector Social Economic Review, 2019)
In this study, it is aimed to show the relationship between ethical leadership, organizational trust, job satisfaction, and intention to leave. The research data was obtained from 421 nurses working in a private university hospital. The reliability and validity of the measurement instrument are tested before. Baron and Kenny’s four step procedures are employed in order to test mediation effect. According to the correlation analysis, there is a significant positive correlation between ethical leadership, organizational trust, and job satisfaction. On the other hand, ethical leadership and organizational trust have a significant negative relationship with turnover intention. As a result of regression analysis, ethical leadership and organizational trust have a meaningful effect on job satisfaction and intention to leave. However, research findings show that the effect of ethical leadership is partly mediated by organizational trust in the effect on job satisfaction and intention to leave.